Pengaruh Opini Audit, Ukuran Perusahaan, Dan Pergantian Manajemen Terhadap Auditor Switching Pada Perusahan Manufaktur Subsektor Makanan Dan Minuman - Amellia Anwar; Amrizal Amrizal (ITB Ahmad Dahlan Jakarta, 2019)
This study aims to analyze the effect of audit opinion, company size and management change on auditor switching in sub-food and beverage manufacturing companies listed on the Stock Exchange for 7 consecutive years. Samples were taken using purposive sampling technique. A sample of 10 companies from 18 sub food and beverage manufacturing companies listed on the Indonesia Stock Exchange in 2011-2017, so that the research data analyzed amounted to 70. The data analysis technique used is descriptive statistics and logistic regression. Based on research results of this study indicate that (1) There is a significant influence of Audit Opinion on the Switching Auditor, the results of testing the size of the company variable produce a wald value of 5.175 with a significance value of 0.023. Because the significance value is smaller than 0.05, then H1 means accepted. (2) The absence of the influence of the Company Size on the Switching Auditor, the result of testing the size of the company variable produces a wald value of 0,000 with a significance value of 0.999. Because the significance value is greater than 0.05, then H2 means rejected (3) The absence of the influence of Management Change on the Switching Auditor, the result of testing the management change variable produces a wald value of 5.175 with a significance value of 0.696. Because the significance value is greater than 0.05, it means that H3 is rejected. (4) Audit Opinion, Company Size and Management Change have an effect simultaneously on the Switching Auditor. This can be seen from the significance value obtained at 0.038 which is smaller than 0.05 so that H4 is accepted.